Photo-Based Nanomedicines Using Polymeric Systems in the Field of Cancer Imaging and Therapy - Patihul Husni; Yuseon Shin; Jae Chang Kim; Kioh Kang; Eun Seong Lee; Yu Seok Youn; Taofik Rusdiana; Kyung Taek Oh (Biomedicines, 2020)
The use of photo-based nanomedicine in imaging and therapy has grown rapidly. The property of light in converting its energy into different forms has been exploited in the fields of optical imaging (OI) and phototherapy (PT) for diagnostic and therapeutic applications. The development of nanotechnology offers numerous advantages to overcome the challenges of OI and PT. Accordingly, in this review, we shed light on common photosensitive agents (PSAs) used in OI and PT; these include fluorescent and bioluminescent PSAs for OI or PT agents for photodynamic therapy (PDT) and photothermal therapy (PTT). We also describe photo-based nanotechnology systems that can be used in photo-based diagnostics and therapies by using various polymeric systems.